X-ray/UV variability and the origin of soft X-ray excess emission from II Zw 177. Issue 1 (27th January 2016) - Pal, Main; Dewangan, Gulab C.; Misra, Ranjeev; Pawar, Pramod K.
Abstract: We study X-ray and UV emission from the narrow-line Seyfert 1 galaxy II Zw 177 using a 137 ks long and another 13 ks short XMM–Newton observation performed in 2012 and 2001, respectively. Both observations show soft X-ray excess emission contributing 76.9 ± 4.9 per cent in 2012 and 58.8 ± 10.2 per cent in 2001 in the 0.3–2 keV band. We find that both blurred reflection from an ionized disc and Comptonized disc emission describe the observed soft excess well. Time-resolved spectroscopy on scales of ∼20 ks reveals strong correlation between the soft excess and the power-law components. The fractional variability amplitude F var derived from EPIC-pn light curves at different energy bands is nearly constant ( F var ∼ 20 per cent). This is in contrast to other active galactic nuclei where the lack of short term variation in soft X-ray excess emission has been attributed to intense light bending in the framework of the 'lamppost' model. Thus, the variations in power-law emission are most likely intrinsic to corona rather than just due to the changes of height of compact corona. The variable UV emission ( F var ∼ 1 per cent) is uncorrelated to any of the X-ray components on short time-scales suggesting that the UV emission is not dominated by the reprocessed emission. The gradual observed decline in the UV emission in 2012 may be related to the secular decline due to the changes in the accretion rate. In this case, the short term X-ray variability is not due to the changes in the seed photons but intrinsic to the hot corona.